A Rare Preterm Newborn Case of Rib Osteomyelitis with Intrathoracic Involvement - seyedeh Fatemeh Khatami (Mashhad University of Medical Sciences, 2017)
Background: Rib osteomyelitis is a very rare form of pediatric osteomyelitis. Case report: Herein, we reported a very rare case of chest wall abscess with rib osteomyelitis and rib destruction due to Staphylococcus aureus infection in a 14-day-old preterm male neonate. The diagnosis of this uncommon disease requires a high index of suspicion due to its rarity and non-specific clinical presentation. The radiographic findings of osteomyelitis usually require 7-14 days to appear. Ultrasonography enabled us to diagnose a coexisting intra- and extra-thoracic solid mass with calcification. In addition, the chest high resolution computed tomography scan revealed rib osteomyelitis, which was not possible to be detected through the routine chest radiography. Following the administration of intensive parenteral antibiotic therapy for 21 days, the patient was discharged in good health condition at 42 days of age. He continued oral clindamycin consumption for the next three weeks. At the end of the six weeks of treatment, the chest X-ray revealed the expansion of the fifth rib end; however, the chest ultrasound showed no obvious fluid collection. Conclusion: As indicated in the present case report, the diagnosis of rib osteomyelitis requires a high index of suspicion given its nonspecific clinical manifestations that can easily mimic other diagnoses .The unusual sites of bone infection could be diagnosed by means of HRCT, followed by ultrasound. The prompt treatment leads to a high cure rate with good prognosis.